2006
DOI: 10.1021/ic050437d
|View full text |Cite
|
Sign up to set email alerts
|

Solution and Structural Investigations of Ligand Preorganization in Trivalent Lanthanide Complexes of Bicyclic Malonamides

Abstract: This report describes an investigation into the coordination chemistry of trivalent lanthanides in solution and the solid state with acyclic and preorganized bicyclic malonamide ligands. Two experimental investigations were performed: solution binding affinities were determined through single-phase spectrophotometric titrations and the extent of conformational change upon binding was investigated with single-crystal X-ray crystallography. Both experimental methods compare the bicyclic malonamide (BMA), which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
3
13
0
Order By: Relevance
“…Homologous ligands with shorter alkyl groups are used instead for crystallography research, since it is argued that they form complexes with an equal coordination environment of a metal. For instance, different‐length alkyl groups in N ‐tetrasubstituted methylmalonamide, ethylmalonamide, and butylmalonamide do not change the coordination environment of a lanthanum(III) central ion in the respective nitrato crystal complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Homologous ligands with shorter alkyl groups are used instead for crystallography research, since it is argued that they form complexes with an equal coordination environment of a metal. For instance, different‐length alkyl groups in N ‐tetrasubstituted methylmalonamide, ethylmalonamide, and butylmalonamide do not change the coordination environment of a lanthanum(III) central ion in the respective nitrato crystal complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Our approach to this problem derives from the premise that preorganization of the malonamide moiety into a conformation resembling that required in the metal−ligand complex will enhance the binding interaction. , In effect, the strain energy, which acyclic ligands 2 experience upon chelation to a metal center, is minimized in the bicyclic ligands 1 . , Initial studies with 1a and 1b showed large enhancements in extraction efficiencies and binding affinities for the bicyclic structures relative to the acyclic analogues, providing strong support for our initial premise. , …”
Section: Introductionmentioning
confidence: 89%
“…in the conformational selection hypothesis), 32 , 33 de novo enzyme design, 34 36 metal binding to proteins, 37 cyclic peptides, 38 supramolecular chemistry, 39 and inorganic chemistry especially when dealing with multidentate ligands. 40 , 41 Although the exact contributions of pre-organization and induced effects in the binding processes are not yet clear – likely depending on the system under investigation – the former offers a possible solution to the absence of a structural template for the Al( iii )–Aβ system. Indeed, plenty of structures of the sole Aβ peptide presenting alternative conformations are available in the Protein Data Bank 42 and suitable algorithms could help in identifying those that satisfy the geometric conditions for the best arrangements of the first coordination sphere of aluminum.…”
Section: Introductionmentioning
confidence: 99%